2016
DOI: 10.1002/met.1553
|View full text |Cite
|
Sign up to set email alerts
|

Medium‐range forecasts of extreme rainfall events during the Indian summer monsoon

Abstract: Extreme rainfall events occur rarely but are integral elements of climatic conditions in any region. The frequency of occurrence of extreme events has been studied using 57 years of observed rainfall data over India and its neighbouring countries. In this study, the rank method has been used to compute the threshold rainfall amount based on past observations. If the model forecasted rainfall is above the climatological threshold, then that event is identified as an extreme at that grid point and for that speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…ISMR exhibits significant temporal and spatial variability (Mooley and Parthasarathy 1984;Thapliyal and Kulshrestha 1991;Kripalani and Kulkarni 2001;Sahai et al 2003;Naidu et al 2015). Several scientists have investigated the inter-annual and intra-seasonal variations of monsoon rainfall and the associated phenomena over the last several years using observed data (Webster et al 1998;Gadgil et al 2003) and conducting modeling studies (Ratna et al 2011;Satyanarayana and Kar 2016;Pattnayak et al 2016a). The key features of Indian summer monsoon include the sudden onset and gradual withdrawal, which signify the beginning and end of the rainy season respectively.…”
Section: Introductionmentioning
confidence: 99%
“…ISMR exhibits significant temporal and spatial variability (Mooley and Parthasarathy 1984;Thapliyal and Kulshrestha 1991;Kripalani and Kulkarni 2001;Sahai et al 2003;Naidu et al 2015). Several scientists have investigated the inter-annual and intra-seasonal variations of monsoon rainfall and the associated phenomena over the last several years using observed data (Webster et al 1998;Gadgil et al 2003) and conducting modeling studies (Ratna et al 2011;Satyanarayana and Kar 2016;Pattnayak et al 2016a). The key features of Indian summer monsoon include the sudden onset and gradual withdrawal, which signify the beginning and end of the rainy season respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The region of highest rainfall coincides with the windward side of the prevailing monsoon southwesterlies; this is due to the earlier onset of the SWM over this region by at least 10 days as observed by Htway and Matsumoto (). While this distribution agrees with the earlier studies (Satyanrayana and Kar, ) where the distinction of south and north regions was identified, this study brings out an additional feature that the rainfall is maximum over the southwest coastal regions decreasing towards the northeast. A small region at the centre with minimum rainfall of <1,000 mm agrees with the arid zone reported by Roy and Kaur ().…”
Section: Resultsmentioning
confidence: 98%
“…APHRODITE rainfall data have been used in several research studies (e.g. Wang et al ., ; Yasutomi et al ., ; Lauri et al ., ; Pai et al ., ; Yatagai et al ., ; Satyanrayana and Kar, ). Monthly rainfall data for the period 2001–2010 at six stations in Myanmar were used for validating the APHRODITE rainfall data used in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies in India on the variability of rainfall and its long term trends (Parthasarathy and Dhar, 1975;Mooley and Parthasarathy, 1984;Sarkar and Thapliyal, 1988;Thapliyal and Kulshresthra, 1991;Guhathakurta and Rajeevan, 2008;Krishnakumar et al, 2009;Kumar et al, 2010;Jain and Kumar, 2012;Bhatla and Tripathi, 2014;Das et al, 2015;Deka et al, 2016;Kothawale and Rajeevan, 2017;Sharma and Singh, 2017). Similarly, there are several studies which focused mainly on the intensity and trends of extreme rainfall events over India, Rakhecha andSoman (1994), Sen Roy andBalling (2004), Joshi and Rajeevan (2006), Rajeevan et al, (2008), Guhathakurta et al, (2010), Gill et al, (2013), Satyanarayana and Kar (2016) and Talchabhadel et al, (2018), to name a few. However, there are only a few studies available on the rainfall variability and trends over northeast India (Das and Goswami, 2003;Das et al, 2011;Deka et al, 2013;Jain et al, 2013;Das et al, 2015;Deka et al, 2016).…”
Section: Introductionmentioning
confidence: 99%